2006
DOI: 10.1088/0953-8984/18/15/002
|View full text |Cite
|
Sign up to set email alerts
|

The glass forming ability of Cu-rich Cu–Hf binary alloys

Abstract: We studied the glass forming ability (GFA) of Cu-rich Cu–Hf binary alloys and found that some of the alloys can be prepared as bulk metallic glasses with maximum diameter up to 2 mm by a conventional Cu-mould casting. The best glass former within the compositional range studied is off-eutectic Cu65Hf35 alloy, which is markedly different from the prediction from the multicomponent and deep eutectic rules. The GFA, thermal stability, kinetics of the glass transition and crystallization for Cu65Hf35 glassy rods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 20 publications
0
36
0
2
Order By: Relevance
“…The small difference in the experimental and predicted compositions was attributed to the fact that the entropy term was neglected in the calculations. Similar work on Cu-Hf alloys (Xia et al, 2006b) and Cu-Zr alloys (Xia et al, 2006c) have confirmed that this method is practical for predicting the best glass-forming compositions, at least in the studied binary alloy systems.…”
Section: The Original Miedema's Model For Binary Alloysmentioning
confidence: 54%
See 1 more Smart Citation
“…The small difference in the experimental and predicted compositions was attributed to the fact that the entropy term was neglected in the calculations. Similar work on Cu-Hf alloys (Xia et al, 2006b) and Cu-Zr alloys (Xia et al, 2006c) have confirmed that this method is practical for predicting the best glass-forming compositions, at least in the studied binary alloy systems.…”
Section: The Original Miedema's Model For Binary Alloysmentioning
confidence: 54%
“…The predicted glass-forming composition range in the Ni-Ti system is 24 -77 at.% Ni, which is in well agreement with the experimental glass-forming composition range (28 -72 at.% Ni) prepared by mechanical alloying. Recently, by combining with a new glass-forming ability parameter, the Miedema's model has been used as a guide to searching for the best glass-forming ability composition in binary alloy systems (Xia et al, 2006a(Xia et al, , 2006b(Xia et al, , 2006c. It is argued that the formation of a metallic glass should involve two aspects (Xia et al, 2006a).…”
Section: The Original Miedema's Model For Binary Alloysmentioning
confidence: 99%
“…The size ratio (q) of small to large particles in the present binary colloid system is 0.69, which is quite similar to the atomic size ratio of Cu-Hf binary alloy (0.6971). It is interesting to find that there are two best glass-forming compositions reported up to now, Cu 55 Hf 45 [9] and Cu 65 Hf 35 [7,8] with the corresponding mixing ratios of 1.22 and 1.86, respectively. The agreement between the colloid mixtures results and the experiment data of binary bulk metallic glasses supports the present experimental design, and gives a direct evidence for the validity of topological factor in determining the glass-forming ability in binary metal liquid.…”
Section: Alloy Systemmentioning
confidence: 95%
“…r small /r large Cu-Zr [10][11][12] 0.7039 Cu-Hf [7][8][9] 0.6971 Ni-Nb [13] 0.7525 Ca-Al [14] 0.6082 that q ranges from 0.55 to 0.80. Here, we use a binary colloid system to simulate the situation of binary BMGs with large particle (d = 2.9 m) and smaller particles (d = 2.0 m).…”
Section: Alloy Systemmentioning
confidence: 99%
See 1 more Smart Citation